Difficulty index in extraction of impacted mandibular third molars and their post-operative complications - Khanal, Pranaya; Dixit, S; Singh, R; Dixit, Punam (Journal of Kathmandu Medical College, 2014)
Background: Although the removal of impacted mandibular third molars is a common minor oral surgical procedure, the extraction of these teeth can present with certain post–operative complications. Koerner KR proposed a Difficulty Index Scale for removal of these teeth on the basis of local anatomy and radiographs, which were helpful in predicting the difficulty that would be encountered intra-operatively, as well as the post-operative complications. Objective: To study the different post-operative complications in the removal of impacted mandibular third molars calculating their difficulty index value. Method: A total of 119 patients, 79 females and 40 males who underwent extraction of their impacted third molars were selected over a one year period. Data were collected prospectively, according to the angulation, depth and position of the impacted mandibular third molars and their difficulty index calculated. This was further correlated with the postoperative complications encountered. Results: Mesio-angular impaction (43.7%), with level A (66.4%) and Class I (70.6%) impaction were the major type of impaction seen. The difficulty index showed that majority were in the moderately difficult category (51.2%), with swelling and trismus seen to increase as the difficulty index value increased. Females were affected more than males, with swelling (Odds ratio 2.206) and trismus (Odds ratio 2.570) seen to be significantly more. Conclusion: Surgical removal of impacted mandibular third molars causes post-operative complications and special care is required in their removal, especially in females. The Difficulty Index, as described by Koerner KR can be used as a tool for predicting the frequency of the post-operative complications, especially swelling and trismus. DOI: http://dx.doi.org/10.3126/jkmc.v3i1.10918 Journal of Kathmandu Medical College Vol. 3, No. 1, Issue 7, Jan.-Mar., 2014, Page: 14-20